2009
DOI: 10.1007/s10493-009-9251-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of three tick defensins and four mammalian cathelicidin-derived synthetic peptides against Lyme disease spirochetes and bacteria isolated from the midgut

Abstract: In this study, chemically synthesized tick defensins and cathelicidin-derived mammalian peptides were used to investigate the activity spectrum against Borrelia garinii and symbiotic Stenotrophomonas maltophila. Synthetic tick defensins showed antimicrobial activity against Staphylococcus aureus but not B. garinii and S. maltophila. Mammalian peptides which have cationic property similar to tick defensins, showed antimicrobial activity similar to tick defensins. The antimicrobial peptides in ticks and mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 13 publications
1
35
0
1
Order By: Relevance
“…However, potential mechanisms employed by the spirochete to evade the innate host response are not well understood yet. It has been demonstrated that unlike many other bacterial pathogens, B. burgdorferi is highly resistant to cathelicidin-derived peptides (27,39), consistent with the spirochete's ability to persistently colonize the skin, where CRAMP is present. Sambri et al (39) suggest that the resistance of B. burgdorferi to antimicrobial peptides may derive from the spirochete's lack of lipopolysaccharide, a negatively charged membrane component to which cationic peptides typically bind (25,43).…”
mentioning
confidence: 93%
“…However, potential mechanisms employed by the spirochete to evade the innate host response are not well understood yet. It has been demonstrated that unlike many other bacterial pathogens, B. burgdorferi is highly resistant to cathelicidin-derived peptides (27,39), consistent with the spirochete's ability to persistently colonize the skin, where CRAMP is present. Sambri et al (39) suggest that the resistance of B. burgdorferi to antimicrobial peptides may derive from the spirochete's lack of lipopolysaccharide, a negatively charged membrane component to which cationic peptides typically bind (25,43).…”
mentioning
confidence: 93%
“…Their mode of action involves electrostatic interaction with the bacterial membrane, leading to permeability changes or pore formation (Sonehshine and Hynes 2008). Our previous work demonstrated that tick defensins with disulfide bridges showed strong killing activity within 1 h against S. aureus but not isolates from the midgut of I. persulcatus (Isogai et al 2009). However, we did not compare the activity between the peptide with tertiary structure and that with primary linear structure.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that Gram-negative bacteria are more sensitive to treatment with cationic antimicrobial peptides. The antimicrobial activities of tick defensins and DefDM are generally known to function against species of Gram-positive bacteria at very low concentrations (Isogai et al 2009;Chrudimská et al 2011Chrudimská et al , 2014. It has been shown that anionic AMPs bind to the St. aureus membrane via interaction with a receptor (Steffen et al 2006) or that AMPs might proteins extracted from normal uninfected Sf9 cells.…”
Section: Discussionmentioning
confidence: 99%